The long wait - Legaspi, Corsie; Lazaro, Cheche (Quezon City Probe Productions, 1991)
The topics dealth with are: the Filipino war veterans of WW II waiting for war benefits from U. S. ; Fr. Corsie Legaspi using divine healing; and a tennis competition against Sweden led by Felix Barrientos.
The long wait (19 min.) -- Divine healing (20 min.) -- Advantage : Philippines (16 min.)
VHS
Reporter, Luchie Cruz-Valdes.
Keywords: World war, 1939-1945 -- Veterans -- Philippines; Spiritual healing -- Philippines; Tennis -- Tournaments